Open Subpectoral Biceps Tenodesis versus Arthroscopic Repair for SLAP Tears in Patients under 30 (224). Issue 10 (31st October 2021) - Colasanti, Christopher; Hurley, Eoghan; Lorentz, Nathan; Campbell, Kirk; Alaia, Michael; Strauss, Eric; Jazrawi, Laith; Matache, Bogdan
Objectives: The purpose of this study is to compare the outcomes of mini-open subpectoral biceps tenodesis (BT) to arthroscopic repair (AR) for SLAP tears in patients under 30. Methods: A retrospective review of patients who underwent either isolated BT or AR for the diagnosis of a SLAP tear was performed. Patients with a follow-up duration of <24 months were excluded. The American Shoulder & Elbow Surgeons (ASES) score, Visual Analogue Scale (VAS), Subjective Shoulder Value (SSV), patient satisfaction, willingness to undergo surgery again, revisions, and return to work/sport were evaluated. A p value of <0.05 was considered to be statistically significant. Results: Our study included 103 patients in total; 29 patients were treated with BT, and 74 were treated with AR. The mean age was 24.8 years, 79.4% were male, and the mean follow-up duration was 60 months. At final follow up, there was no difference between treatment groups in any of the functional outcome measures assessed (p > 0.05). Overall, there was no significant difference in the total rate of RTP (BT: 76.3%, AR: 85%; p = 0.53), timing of RTP (BT: 8.8 months, AR: 9.4 months; p = 0.61), and total rate of RTP among overhead athletes (BT: 84.2%, AR: 83.3%; p = 1). However, there was a significantly lower rate of revision surgery with BT (0%) as compared to AR (14.1%; p = 0.03). Conclusions: In patients under the age of 30 with isolated SLAP tear pathology, BT is a reliable alternative to AR, with a low rate of revision surgery, and excellent patient reported outcomes.